Rhizosphere microbiomes of field-grown B. stricta exhibit minimal diel changes in microbial membership and protein synthesis potential - Ceretto, Alessandra; Weinig, Cynthia (Frontiers in Microbiology, 2025)
The rhizosphere microbiome has a significant impact on plant health and fitness. Quantifying bacterial responses to fine-scale plant-mediated changes in the rhizosphere, such as those associated with diel cycling in host plant physiology, will increase our understanding of microbial community assembly patterns. Here, we used 16S rRNA biomarker gene (DNA) and transcript (RNA) sequencing to characterize changes in the rhizosphere community membership and PSP over short timescales in field-grown Boechera stricta (B. stricta) plants. Microbial communities characterized by 16S-rRNA-transcripts, which serve as a proxy for microbial protein synthesis potential (PSP), showed greater sensitivity to fine-scale environmental changes than did communities characterized by 16S-rRNA biomarker gene sequencing, which reflects microbial presence/absence. Significant differences were observed between communities characterized by RNA vs. DNA, with RNA-derived communities showing greater alpha and beta diversity differences between the rhizosphere vs. control soil communities within phyla and in differential abundance analysis of genera. Communities reconstructed from RNA were more sensitive to the effects of field blocks and collection timepoints. Differential abundance analysis revealed significant differences (p < 0.05) between the pre-dawn (AM) and early afternoon (PM) timepoints for five genera based on 16S rRNA transcripts. This included the plant-associated genus Curtobacterium. However, when variance was partitioned between days of collection, the amplitude of the signal between diel timepoints was non-significant. In summary, community composition and protein synthesis potential were highly sensitive to abiotic factors expressed over the small spatial scale of field blocks and short 24-h periods between collection days but showed minimal to no diel patterning.